Effect of dual antiplatelet therapy prolongation in acute coronary syndrome patients with both high ischemic and bleeding risk: insight from the OPT-CAD study - Na, Kun; Qiu, Miaohan; Wei, Ningxin; Li, Jiayin; Yan, Chenghui; Li, Jing; Li, Yi; Han, Yaling (Frontiers in Cardiovascular Medicine, 2023)
Backgrounds: In current clinical practice, controversy remains regarding the clinical benefits of prolonged DAPT in ACS patients facing high risks of both ischemia and bleeding ("bi-risk") following PCI. This study aimed to investigate the feasibility of identifying bi-risk ACS patients after PCI using the OPT-BIRISK criteria, emphasizing extended DAPT treatment safety and efficacy beyond 12 months in these bi-risk ACS after PCI in real-world conditions. Methods: This analysis compared extended DAPT and SAPT at 12–24 months in ACS patients undergoing PCI with both ischemic and bleeding risk defined by OPT-BIRISK criteria. This was a post–hoc analysis of the OPT–CAD study. The main research outcome was the incidence of ischemic events within 12 to 24 months, composite of stroke, myocardial infarction, and cardiac death events. For the external validation of the OPT-BIRISK criteria to identify a bi-risk ACS patient, ischemic events, BARC 2, 3, 5 bleeding events, and BARC 3, 5 bleeding events at 5 years were analyzed. Results: The total number of ACS patients analyzed in this analysis was 7,049, of whom 4,146 (58.8%) were bi-risk patients and 2,903 (41.2%) were not. The frequency of ischemic events was significantly different between the two groups at 5 years (11.70% vs. 5.55%, P < 0.001), and the incidence of BARC 2,3,5 bleeding was significantly higher in the bi-risk group (6.90% vs. 4.03%, P < 0.001) than in the non-bi-risk group. Among the bi-risk patients without any clinical adverse events within 12 months that underwent extended DAPT treatment (n=2,374, 75.7%) exhibited a lower risk of stroke at 12-24 months (1.10% vs. 2.10%, P = 0.036) relative to those that underwent SAPT (n=763, 24.3%), while bleeding risk did not differ significantly between these groups. Conclusions: In conclusion, the findings showed that using the OPT-BIRISK criteria could help physicians identify ACS patients at a high risk of developing recurrent ischemia and bleeding episodes after PCI. Compared to antiplatelet monotherapy, a strategy of extended DAPT may offer potential benefits in lowering the risk of stroke without carrying a disproportionately high risk of serious bleeding problems among these patients who were event-free after a year of DAPT.